Effect of eyestalk ablation and water temperature on the gonadal transcriptome of greasyback shrimp (Metapenaeus ensis) - Xinhe Ruan; Huitao Cheng; Jinhong Shan; Lihua Li; Zijie Xuan; Kaishan Liang; Xianze Jia; Jie Yu; Zongyang Li; Liyuan Luo; Xiaoling Zuo; Kun Wu; et al. (Aquaculture Reports)
Metapenaeus ensis (De Haan 1850), a commercially viable species in China, has yet to be studied in depth, particularly with regard to gonadal development. Understanding the dynamics of gonadal development is crucial for the successful culture of this shrimp. To this end, we conducted a comparative analysis of the gonadal transcriptomes of M. ensis using Illumina RNA-seq technology. Our study aimed to identify gonad-related genes by comparing gonadal transcriptomes after two key methods of stimulating gonadal development in females and males: eyestalk ablation and temperature stress. A total of 54,425 unigenes were obtained after assembly and annotated in the database, yielding 25,715 unigenes. Differentially expressed gene (DEG) analysis was performed on male and female gonads post-eyestalk ablation gonads and post-temperature stress and compared to controls. The DEGs showed functional enrichment in KEGG pathways related to DNA replication, starch and sucrose metabolism, and mitochondrial autophagy. A total of 17 DEGs known to be associated with gonadal development were searched in the transcriptome of M. ensis. Female-specific DEGs, including VG, VGR, AK, PGFS, CYP49A1, SRM, and PGES2, and male-biased DEGs, including IGF1R, SPATA20, DMRT1, INSR, SPATA2, SPATA13, GNRHR, MPRS-γ, SMOX, and FOXJ2–3, were identified. This study also demonstrated the capacity to regulate the expression of CHH and SPATA13 following eyestalk ablation, as well as the capacity to regulate the expression of HSP70 and MIH following temperature stress, subsequently impacting gonadal development. These results highlight the genes involved in gonadal development, which will enhance our understanding in further studies on the reproduction and breeding of M. ensis and other marine crustacea.